2015
DOI: 10.12691/jfnr-3-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Human Breast Cancer Cells Treated with <i>Monascus</i>-Fermented Red Mold Rice Extracts

Abstract: Monascus-fermented red mold rice (RMR) extracts have recently been proved to possess anticancer activities, but the anticancer effect of breast cancer cells treated with RMR is not yet well understood. In an effort to identify proteins that may be involved in RMR-induced breast cancer cell death, we employed proteomic analysis coupled with LC-nanoESI-MS/MS on MCF-7 cells exposed to two RMR extracts, ethyl acetate extract (EAE) and ethanol extract (EE). Sixupregulated proteins were identified in EAE-induced MCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Furthermore, fermented foods can possess biological activities that include anti-aging, anti-oxidant, anti-cancer and anti-obesity properties [13]. Studies have shown that rice [14], coix seed [15] and sorghum liquor biowaste [16] fermented with Monascus have anticancer activity. Our earlier research demonstrated that fish bone fermented with Monascus purpureus (M. purpureus) (FBF) can enhance anti-oxidant ability and reduce inflammatory effects, which is attributable to increased total phenols and functional amino acid content by fermentation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fermented foods can possess biological activities that include anti-aging, anti-oxidant, anti-cancer and anti-obesity properties [13]. Studies have shown that rice [14], coix seed [15] and sorghum liquor biowaste [16] fermented with Monascus have anticancer activity. Our earlier research demonstrated that fish bone fermented with Monascus purpureus (M. purpureus) (FBF) can enhance anti-oxidant ability and reduce inflammatory effects, which is attributable to increased total phenols and functional amino acid content by fermentation [17,18].…”
Section: Introductionmentioning
confidence: 99%